Recent kinematics of the tectonic plates surrounding the Red Sea and Gulf of Aden. Issue 1 (30th July 2016) - Schettino, Antonio; Macchiavelli, Chiara; Pierantoni, Pietro Paolo; Zanoni, Davide; Rasul, Najeeb
Abstract: The Red Sea and Gulf of Aden represent two young basins that formed between Africa and Arabia since the early Oligocene, floored by oceanic crust or by transitional and thinned continental crust. While in the easternmost Gulf of Aden, the rift–drift transition can be dated chron C6 (∼20.1 Ma), here we show that in the Red Sea the first pulse of seafloor spreading occurred during chron C3n.2n (∼4.6 Ma) around ∼17.1°N (present-day coordinates) and propagated southwards from this location, separating the Danakil microplate from Arabia. It is also shown that seafloor spreading between Arabia and Nubia started later, around chron 2A (∼2.58 Ma), and propagated northwards. At present, there is no magnetic evidence for the existence of a linear spreading centre in the northern Red Sea at latitudes higher than ∼24°N and in the southern Red Sea below ∼14.8°N. The present-day plate kinematics of this region can be described with high accuracy by a network of five interacting plates (Nubia, Arabia, Somalia, Sinai and Danakil) and six triple junctions. For times older than anomaly 2A (∼2.58 Ma) and up to anomaly 3, the absence of marine magnetic anomalies between Arabia and Nubia prevents a rigorous kinematic description of the five-plates system. However, there is strong evidence that the unique changes in plate motions during the last 5 Myr were a dramatic slowdown at chron C2 (∼1.77 Ma) in the spreading or extension rates along the ridge and rift axes, thereby a good representation of the real plate motions can be obtained anyway by backward extension of the oldest Arabia–Nubia and Arabia–Danakil stage rotations determined on the basis of marine magnetic anomalies, respectively, C2–C2A and C2A–C3. The proposed kinematic reconstructions are accompanied by a geodynamic explanation for the genesis of large continent–continent fracture zones at the rift–drift transition and by an analysis of the strain associated with plate motions in Afar, northeastern Egypt and Sinai.